Integrative Bioinformatics Study of Tangeretin Potential Targets for Preventing Metastatic Breast Cancer. (14th July 2021) - Hermawan, Adam; Putri, Herwandhani; Hanif, Naufa; Ikawati, Muthi
Abstract : Agents that target metastasis are important to improve treatment efficacy in patients with breast cancer. Tangeretin, a citrus flavonoid, exhibits antimetastatic effects on breast cancer cells, but its molecular mechanism remains unclear. Tangeretin targets were retrieved from PubChem, whereas metastatic breast cancer regulatory genes were downloaded from PubMed. In total, 58 genes were identified as potential therapeutic target genes of tangeretin (PTs). GO and KEGG pathway enrichment analyses of PTs were performed using WebGestalt (WEB-based Gene SeT AnaLysis Toolkit). The PPI network was analyzed using STRING-DB v11.0 and visualized by Cytoscape software. Hub genes were selected on the basis of the highest degree score as calculated by the CytoHubba plugin. Genetic alterations of the PTs were analyzed using cBioPortal. The prognostic values of the PTs were evaluated with the Kaplan–Meier plot. The expression of PTs across breast cancer samples was confirmed using GEPIA. The reliability of the PTs in metastatic breast cancer cells was validated using ONCOMINE. Molecular docking was performed to foresee the binding sites of tangeretin with PIK3C α, MMP9, PTGS2, COX-2, and IKK. GO analysis showed that PTs participate in the biological process of stimulus response, are the cellular components of the nucleus and the membrane, and play molecular roles in enzyme regulation. KEGG pathway enrichment analysis revealed that PTs regulate the PI3K/Akt pathway. Genetic alterations for each target gene were MTOR (3%), NOTCH1 (4%), TP53 (42%), MMP9 (4%), NFKB1 (3%), PIK3CA (32%), PTGS2 (15%), and RELA (5%). The Kaplan–Meier plot showed that patients with low mRNA expression levels of MTOR, TP53, MMP9, NFKB1, PTGS2, and RELA and high expression of PIK3CA had a significantly better prognosis than their counterparts. Further validation of gene expression by using GEPIA revealed that the mRNA expression of MMP9 was significantly higher in breast cancer tissues than in normal tissues, whereas the mRNA expression of PTGS2 showed the opposite. Analysis with ONCOMINE demonstrated that the mRNA expression levels of MMP9 and NFKB1 were significantly higher in metastatic breast cancer cells than in normal tissues. The results of molecular docking analyses revealed the advantage of tangeretin as an inhibitor of PIK3CA, MMP9, PTGS2, and IKK. Tangeretin inhibits metastasis in breast cancer cells by targeting TP53, PTGS2, MMP9, and PIK3CA and regulating the PI3K/Akt signaling pathway. Further investigation is needed to validate the results of this study.